Plasmon mediated near zero-reflection of TiO2/Ag-nanoislands/Si multilayer structure. (10th May 2019) - Dewasi, Avijit; Arya, Mahima; Mitra, Anirban
Abstract: In addition to conventional antireflection coating with high dielectric constant like TiO2, plasmonic properties of silver (Ag) nanoislands could be used to improve the antireflection property and consequently tune its window. Here, we have reported the possibility of achieving near zero-reflection (0.43%) condition and tunability of its window for TiO2 /Ag-nanoislands/Si multilayer structure fabricated using pulsed laser deposition technique. An optimized thickness of TiO2 layer has been deposited to fulfill the requirements of desired reflection property for the proposed structure. Plasmonically more sensitive closely packed metal nanoislands have been used to achieve the tunability of near zero-reflection window in the wavelength range 576 nm to 732 nm. A systematic analysis has been carried out to develop a better insight of the physical mechanism behind the phenomena using theoretical model and spectroscopic ellipsometer. The proposed theoretical model, as reported earlier, has been applied to predict the effective plasmonic response of Ag nanoislands embedded in between TiO2 and Si substrate. This also helps us in spectroscopic ellipsometric characterization of the proposed structure which eventually supports the LSPR induced tuning of antireflection window.